Smart multi-responsive aramid aerogel fiber enabled self-powered fabrics. (October 2022) - Zuo, Xingwei; Fan, Tingting; Qu, Lijun; Zhang, Xueji; Miao, Jinlei
Abstract: Wearable electronics and systems with self-powered real-time responses to various stimuli, such as mechanical, electrical, thermal and optical signals，are eagerly desired, however still remain great challenges. Herein, smart fibers with multi-response to external stimuli are developed via wet spinning porous aramid aerogel nanofibers while utilized as a three-dimensional hierarchical percolating skeleton for silver nanowires (AgNWs) interwoven MXene conductive network. The coaxial AgNWs/MXene@ aramid aerogel nanofibers with entangled heterostructures effectively avoid "trade-off" effect between high electrical conductivity and mechanical flexibility of smart fibers. Meanwhile, the hierarchical porous structure of aerogel conductive fibers induced strong capillary force and confinement to polyethylene glycol, which has a wide range of phase transition temperature and huge enthalpy to store tremendous thermal energy. After further encapsulated with transparent fluorosilicone resin, the stabilized smart fiber exhibits excellent self-cleaning properties with water and oil repellent. Furthermore, the woven aerogel fabrics coupled with thermoelectric generator realized efficient reversible energy conversion and storage as well as solar-thermal-electrical power generation for all-weather electricity power supply, which could drive the operation of wearable electronics and car models without batteries, providing an efficient strategy for outdoor travel and lunar rover continuous operating. The smart aramid aerogel fibers and fabrics hold great promise for next generation of self-powered wearable systems. Graphical Abstract: ga1 Highlights: Multi-responsive aramid aerogel fiber enabled smart fabrics was successfully developed via large-scale wet spinning. Hierarchically porous structure of aerogel fiber induced strong capillary force and confinement to energy storage materials. The smart aerogel fiber improved the electrical/thermal conductivity of PCMs for rapid thermal energy response and storage. The aerogel fabrics realized reversible solar-thermal-electrical power generation for all-weather electricity power supply. The smart aramid aerogel fiber providing an efficient strategy for outdoor travel and lunar rover continuous operating.